Bridging Patient Education and Cardiac Health: Nursing Interventions in ECG-based Monitoring and Counselling. - Sulaiman Alkahtani, Abdulmohsen; Al Massrahi, Mona Abdullah; aldosary, Salma hassan; Alqahtani, Mohammed Wazi; Alasmari, Saleha Abdullah; Alghannam, Bandar Mohammad; Alsuwayhib, Haya saad; Aldawsari, Nasser Mohammed (Journal of Neonatal Surgery, 2025)
Background: Cardiovascular diseases (CVDs) remain the leading global cause of death, with rising incidence in India due to sedentary lifestyles, poor diet, and inadequate preventive care. Early detection and education are vital to reducing morbidity and mortality. Electrocardiogram (ECG) monitoring serves as a cornerstone for identifying arrhythmias, ischemia, and conduction abnormalities; however, limited awareness and poor patient understanding hinder its full potential. Nurse-led education and counselling have emerged as powerful strategies to bridge gaps between clinical diagnosis and patient comprehension, empowering individuals to actively engage in cardiac self-care. Methodology: This narrative review integrates global and Indian literature, interventional studies, and nursing models such as Orem’s Self-Care Theory and the Health Belief Model. It explores nurse-led ECG monitoring, patient education techniques, technological integration including digital ECG systems, tele-nursing, and AI-assisted interpretation and evaluates outcomes from clinical trials, highlighting improvements in knowledge, adherence, and cardiac risk reduction. Results: Evidence demonstrates that nurse-driven ECG education and counselling significantly enhance patient understanding, medication adherence, and lifestyle modification, leading to reduced hospital readmissions and improved quality of life. Technological integration through tele-cardiology, mobile ECG apps, and AI platforms strengthens accessibility and diagnostic precision. Nonetheless, barriers such as inconsistent nurse training, limited institutional support, health literacy gaps, and ethical concerns in digital monitoring persist. Conclusion: Nurse-led ECG-based education is an effective and scalable approach to improving cardiac literacy and outcomes. Strengthening nurse training, integrating technology responsibly, and embedding supportive policies will advance equitable cardiac care. Future directions include wearable ECG sensors, AI-driven monitoring, and virtual simulation training to further enhance cardiac nursing competencies and patient empowerment